Effects on of dexamethasone on vaccination responses against pneumonic pasteurellosis in goats - Abdul Razak, Intan Shameha; Saad, Mohd Zamri (Veterinary Association Malaysia, 2005)
A study was conducted to compare the effect of dexamethasone treatment prior to, during and post-vaccination on antibody response and protection against experimental challenge with Mannhaemia haemolytica. Sixteen goats of about 7 months old were divided into 4 equal groups. All goats were vaccinated twice intranasally with 1 ml inoculum containing 106 colony forming unit (cfu) of formalin-killed Mannhaemia haemolytica A2/ml. The two doses were administered at 2-week intervals. Goats in group 1 were treated with dexamethasone prior to vaccination, group 2 was treated during vaccination, group 3 was treated at 1 week-post vaccination while group 4 remained as the vaccinated control. Serum samples were collected weekly for a period of 5 weeks to detect antibody using an ELISA. Two weeks post-vaccination, all goats were challenged intratracheally with 4 ml inoculum containing live Mannhaemia haemolytica at a concentration of 109 cfu/ml before slaughtering at 2 weeks post-challenge. The extent of pneumonic lung lesions was determined. Generally, animals without dexamethasone treatment had significantly (p<0.05) high antibody response compared to other groups while the extent of pneumonic lung lesions was significantly (p<0.05) lowest. Although group 1 showed the second highest antibody response and a lower percentage of lesions, the differences were significant (p<0.05) compared to the control group. Group 2 which showed the second lowest antibody response recorded significantly (p<0.05) extensive lung lesions while group 3, which showed the lowest antibody level had insignificantly (p<0.05) more extensive lung lesions. There were strong correlations between the antibody response and the severity of lesions. The results emphasise that vaccination will not be efficient if carried out when the animal is under stressful conditions.